1986
DOI: 10.1177/101269028602100104
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Brazilian Children's Socialization into Sport

Abstract: In an attempt to apply a social role-social systems approach to study the sport socialization process of children. a fixed-alternative questionnaire was administered to Brazilian children in Sāo Paulo. When testing the general model, results from multiple regression analyses on 94 males and 77 females revealed that values of parents, family, peers, opportunity set and teachers strongly influenced the process of becoming involved in sport. Stepwise regressions revealed that the model was a better predictor of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…For example, girls are less encouraged by family and friends to participate in physical activity and sports (Goellner et al, 2010;Silva, Gomes, & Goellner, 2008). In another study, although somewhat dated, Greendorfer, Blinde, and Pellegrini (1986) reported that 'the family does not seem to support female participation; yet, at the same time, it is extremely supportive for male participation' (p. 58). Our objective with the present study was to gain a contemporary view of gender performance in the context of FMS performance in children aged 3-10 years.…”
Section: Gender Differences In Brazilian Children's Fundamental Movemmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, girls are less encouraged by family and friends to participate in physical activity and sports (Goellner et al, 2010;Silva, Gomes, & Goellner, 2008). In another study, although somewhat dated, Greendorfer, Blinde, and Pellegrini (1986) reported that 'the family does not seem to support female participation; yet, at the same time, it is extremely supportive for male participation' (p. 58). Our objective with the present study was to gain a contemporary view of gender performance in the context of FMS performance in children aged 3-10 years.…”
Section: Gender Differences In Brazilian Children's Fundamental Movemmentioning
confidence: 92%
“…First is consideration of the home and family -research indicates that female participation in physical activity and sport is not supported as it is with males (Greendorfer et al, 1986). Similarly, although the sample was older, Gonçalves, Hallal, Amorim, Araújo, and Menezes (2007) reported that Brazilian male adolescents had more social and family support to engage in physical activities than did female adolescents.…”
Section: Early Child Development and Carementioning
confidence: 93%
“…Social scientists have become increasingly concerned with children's participation in competitive sport and the outcomes from such experiences (Greendorfer et al, 1986). These investigations have established that children are introduced to sport through a socialization process defined as one "whereby individuals learn skills, traits, values, attitudes, norms, and knowledge associated with the performance of anticipated social roles" (McPherson & Brown, 1988, p. 267).…”
Section: Review Of Literature Sport Socializationmentioning
confidence: 99%
“…Further, while previous research has examined the socialization processes of Hispanic/Latino youth athletes and youth athlete parents, there is little research aimed at examining these processes for elite-level athlete participants (e.g., Dawes, Modecki, & Gonzales;2015;Dorsch et al, 2015;Erkut, Fields, Sing, & Marx, 1996;Erkut & Tracy, 2002;Greendorfer et al, 1986). Therefore, this current investigation will provide researchers and practitioners with evidence of successful socialization processes that can be encouraged in order to generate more meaningful and more consistent sport participation among Hispanic/Latina women in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation